2014
DOI: 10.1016/j.tim.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax lethal and edema toxins in anthrax pathogenesis

Abstract: The pathophysiological effects resulting from many bacterial diseases are caused by exotoxins released by the bacteria. Bacillus anthracis, a spore-forming bacterium, is such a pathogen, causing anthrax through a combination of bacterial infection and toxemia. B. anthracis causes natural infection in humans and animals and has been a top bioterrorism concern since the 2001 anthrax attacks in the USA. The exotoxins secreted by B. anthracis use CMG2 as the major toxin receptor and play essential roles in pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
196
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 186 publications
(201 citation statements)
references
References 98 publications
2
196
0
3
Order By: Relevance
“…TEM8 was the first toxin receptor to be described (4) and continues to receive attention as a potential tumor marker. CMG2 appears to be expressed more widely in tissues, has a higher affinity for PA (6), and in our work has been found to be more important for both bacterial pathogenesis (8,22) and tumor targeting (16,21).…”
Section: Discussionsupporting
confidence: 60%
“…TEM8 was the first toxin receptor to be described (4) and continues to receive attention as a potential tumor marker. CMG2 appears to be expressed more widely in tissues, has a higher affinity for PA (6), and in our work has been found to be more important for both bacterial pathogenesis (8,22) and tumor targeting (16,21).…”
Section: Discussionsupporting
confidence: 60%
“…In analogy to the mechanism of action of anthrax 29 or diphtheria toxins, 30 transmembrane proteins might also be engineered to transport molecules into the cytosol of target cells. [31][32][33][34] We have shown that ClyA nanopores can be engineered to selectively internalize proteins into the nanopore interior.…”
Section: Introductionmentioning
confidence: 99%
“…While examining sequences related to HipA, we noticed limited but significant sequence similarity between HipA and a family of proteins known as spore coat protein H (CotH). CotH orthologs are found in many bacterial and eukaryotic species, including several human pathogens, such as the spore-forming bacterium Bacillus anthracis and the spore-forming fungi Rhizopus oryzae, the causative agents of anthrax and mucormycosis, respectively (20,21). CotH is a component of the spore coat, a multilayered shell consisting of ∼70 proteins that are assembled into layers by regulatory proteins referred to as morphogenetic factors (22).…”
mentioning
confidence: 99%